Gender Differences in Elderly With Subjective Cognitive Decline - Wang, Lijun; Tian, Ting; , Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2018)
Objective: Subjective cognitive decline (SCD), also known as significant memory concern (SMC), has been suggested as a manifestation of Alzheimer’s Disease (AD) preceding mild cognitive impairment (MCI). This study assessed the impact of gender on cognition, amyloid accumulation, the volumes of hippocampus, entorhinal cortex (EC), fusiform and medial temporal lobe (MTA) and cerebrospinal fluid (CSF) pathology biomarkers in patients reporting SMC. Methods: Twenty-nine males (mean age ± SD: 72.3 ± 5.7 years) and 40 females (mean age ± SD: 71.0 ± 5.1 years) with SMC from the AD Neuroimaging Initiative (ADNI) were included in the study. We explored the gender discrepancies in cognition, [18F] AV45 amyloid positivity, volumes of hippocampus, EC, fusiform and MTA and CSF biomarkers. Results: Compared with females, males showed significantly worse performance in Assessment Scale-cognitive subscale 13 (ADAS-13; P = 0.004) and lower amyloid deposition (P < 0.001). However, females showed greater advantage on the task of Rey Auditory Verbal Learning Test-5 (RAVLT-5) sum (P = 0.021), RAVLT-immediate recall (P = 0.010) and reduced volumes of the hippocampus, EC, fusiform and MTA (P = 0.001, P < 0.001, P < 0.001, P = 0.007) than males. No gender differences were found in CSF Aβ42, CSF Tau and CSF P-tau (P = 0.264, P = 0.454, P = 0.353). Conclusions: These findings highlight that gender discrepancies should be considered in the interpretation of cognitive measures when evaluating SMC.